Safety And Efficacy Of Losartan (50 Mg) In Post Dialysis Euvolemic Hypertensive Patients: A Single-Blind Randomized Control Trial - Aftab, Raja Ahsan (2018)
Patients with End Stage Renal Disease (ESRD) require lifelong fluid replacement therapy or renal transplant. Almost 60-90 % haemodialysis patients are hypertensive. Studies aimed at elucidating the pathophysiology of hypertension among haemodialysis patients concluded that 90% cases resulted from sodium and volume overload (volume-dependent), while the majority of the remaining cases have elevated renin activity (renin dependent), leading to renin dependent high blood pressure. Since there is a constant volume variation during dialysis session, there is a strong possibility for activation of Renin Angiotensin Aldosterone System (RAAS) during dialysis that causes high blood pressure even if they are post dialysis euvolemic.